2018
DOI: 10.18006/2018.6(6).919.928
|View full text |Cite
|
Sign up to set email alerts
|

MAIZE (Zea mays l.) RESPONSE TO MYCORRHIZAL FERTILIZATION ON FERRUGINOUS SOIL OF NORTHERN BENIN

Abstract: The use of Arbuscular Mycorrhizal Fungi (AMF) is considered one of the effective organic ways to increase the crops productivity. The aim of this study was to evaluate the growth promoting effect of three mycorrhizal fungi (Glomus cubense, Rhizophagus intraradices and Funneliformis mosseae) on maize crops in a ferruginous soil of Northern Benin. Maize seeds were inoculated with mycorrhizal fungi in combination with or without minerals fertilizer. Study was conducted in a completely randomized block design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…+ 50% of recommended N 15 P 15 K 15 + Urea. Similar results have been reported by several authors, who have shown in their work that in general, the frequency of mycorrhization of inoculated plants is high, while the intensity of mycorrhization remains low (Haro, 2016;Koda et al, 2018). Indeed, according to Diagne and Ingleby (2003), the level of infection does not have to be very high to be beneficial to the plant.…”
Section: Discussionsupporting
confidence: 87%
“…+ 50% of recommended N 15 P 15 K 15 + Urea. Similar results have been reported by several authors, who have shown in their work that in general, the frequency of mycorrhization of inoculated plants is high, while the intensity of mycorrhization remains low (Haro, 2016;Koda et al, 2018). Indeed, according to Diagne and Ingleby (2003), the level of infection does not have to be very high to be beneficial to the plant.…”
Section: Discussionsupporting
confidence: 87%
“…Similar efficacy of G. fasciculatum on the growth and performance of normal and regenerated Andrographis paniculata plants has been studied [58]. Numerous works have shown the effectiveness of endomycorrhizal symbiosis in improving maize productivity [59][60][61][62][63].…”
Section: Infected Corn Roots Colonized By Shrub-shaped Mycorrhizal Fu...mentioning
confidence: 99%
“…The lowest TN content in degraded soils was due to C:N stoichiometry, soil erosion, and lack of continuity of N fertilization. Likewise, a significantly lower amount of AP in degraded soils was likely associated with lack of P fertilization and higher P fixation by ferruginous minerals (Yimer et al, 2007;Koda et al, 2018). While P fixation is a problem in Ferrallitic-ferruginous soils, the higher TOC content in horticulture soils might have decreased P fixation and increased AP (Moges et al, 2013;Kalu et al, 2015).…”
Section: Impact Of Land-use Changes On Soil Propertiesmentioning
confidence: 99%